Physical, structural and optical characterization of silica-borotellurite glasses containing vanadium and nickel ions - Mohd Nor, Nurhayati; Mohamed Kamari, Halimah; Abdul Latif, Amirah; Mohd Shah, Nurisya; Shahrol Nidzam, Nazirul Nazrin; Yusof, Nur Nabihah; Boukhris, Imed; Kebaili, Imen (Elsevier, 2021)
Silica borotellurite glasses with compositions SiO2][SiO2][SiO2] 0.2}0.99{V2O5}0.01]1-z (Ni0)z (where z = 0.005,0.010,0.015,0.020 and 0.025 M fraction) had been prepared by conventional melt quenching technique. XRay Diffractograms spectra confirm the amorphous nature of the prepared glasses. Study of infrared (IR) spectroscopy reveals an increase in the formation of nonbridging oxygens (NBOs) as nickel concentration increases. This resulted in the decrease of density and oxygen packing density (OPD) of the glass. The observed ESR spectra confirmed that V4+ ions exist as vanadyl ion in the octahedral coordination with tetragonal compression. Based on UV–vis absorption spectra, four absorption bands have been observed with indirect optical band gap, Urbach’s energy, refractive index and other optical parameters have been calculated. The Ni2+ ions were distributed with octahedral and tetrahedral coordination of the ligand field. Nevertheless, the octahedral coordination of Ni2+ dominated over tetrahedral coordination with the increase of NiO concentration consequently, confirmed the increase in NBOs from the IR spectra. These observations reflect the decrease in optical band gap, metallization criterion and the increase in Urbach’s energy and refractive index.